(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The rich bibliographical review on Hierapolis of Phrygia (Turkey), where for more than fifty years italian archaeologists have been working, gives useful information not only about the most recent publications on the site and on the archaeological excavations, but also about the other media of scientific and popular communication, such as multimedia supports and web sites. So a more comprehensive consideration rises, how much the work of one of the most important and fruitful italian archaeological missions abroad is an example of the scientific duties of the Directors of the excavations at a big urban context: the importance of the setting, the planning and of publishing the results of an extensive, big size excavation.